Measurement of tethered swimming power for water polo player by using electromagnetic brake-type ergometer - Wakayoshi, K.; Minami, T.; Taima, N.; Watanabe, Y.; Ohashi, K. (The Journal of Physical Fitness and Sports Medicine, 2017)
[Aims] Water polo players playing ball games in the water are required to have swimming power to overcome water resistance and power to move powerfully in body contacts. In this research, we aim to establish a simple evaluation method for measuring the tethered swimming power in the specific motion required for water ball game. [Methods] Subjects are five male players including three Japanese national players and two old players. Subjects performed the maximal effort swimming of arm scrolling with eggbeater kick. An electromagnetic brake type ergometer as a load device was used to investigate the relationship between tethered load and speed. The load was set in some stages in the range of 0.3 to 3.0 kp, and the pulling time was set to 15 sec. In the previous study, the relationship between the load (x) and the speed (y) becomes y=-ax+b, the power (y) is y=x(-ax+b). When this equation of y=-a(x-b/2a)2+b2/4a, is, x-b/2a=0, the maximum tethered swimming power is obtained by b2/4a. [Results] There was a remarkable linear relationship between tethered load and speed for all subjects (r>0.980). Maximum tethered swimming power was obtained from regression line equation of each subject. The highest values was 68.1 watt for Japanese national player. [Conclusions] Even it would be a difference in the subject`s physical strength, it is thought that the method in this study is effective in evaluating the swimming performance of water polo players.